33. Dosimetric study of parametral implantation of interstitial needles in uterovaginal pulsed dose rate brachytherapy. (December 2017) - Vande Woestyne, M.; Champagne, C.; Roque, A.; Mathieu-Régnier, É.; Servagi Vernat, S.; Gaillot-Petit, N.
Abstract : Introduction: To evaluate retrospectively the dosimetric benefit of adding interstitial needles (IN) to intracavitary applicators in locally advanced cervical cancer brachytherapy. Methods: (1) Ten patients cases treated for a cervical cancer whose hysterectomy pathologic specimens showed macroscopic residual disease. The residual disease area was delineated a posteriori. They have been re-planned, adding virtual IN, considering delineation. The prescribed dose was 15 Gy with pulsed dose rate brachytherapy. DVH data of CTV HR (high risk), CTV IR (intermediate risk), residual disease area and organs at risk (OARs) were compared with and without IN. (2) 22 patients cases treated with AI since 2013 November. They have been re-planned, removing IN, with dosimetric optimization and respecting OARs constraints. Results: (1) three IN per patient were virtually added with a mean active length of 20 mm. In the group with IN, HR-CTV has been improved by 3.75 Gy (±3.41) for D90 (p = 0.021), 2.20 Gy (±1.88) for D100 (p = 0.024) and 11.65% for V85 (p = 0.038). The dosimetric gain to residual disease volume was not significant. Besides, no significant dosimetric difference was found for OARs. (2) three IN per patient were removed with a mean active length of 20 mm. Suppression of AI decreased significantly HR-CTV by 7.47% and RI-CTV by 10.12% (p < 0.004). No significant dosimetric difference was found for OARs. Conclusion: Adding interstitial needles to intracavitary brachytherapy applicator improves dose coverage of HR-CTV, while respecting OARs constraints.